2008
DOI: 10.1242/jeb.023903
|View full text |Cite
|
Sign up to set email alerts
|

Weight and nutrition affect pre-mRNA splicing of a muscle gene associated with performance, energetics and life history

Abstract: SUMMARYA fundamental feature of gene expression in multicellular organisms is the production of distinct transcripts from single genes by alternative splicing (AS), which amplifies protein and functional diversity. In spite of the likely consequences for organismal biology, little is known about how AS varies among individuals or responds to body condition, environmental variation or extracellular signals in general. Here we show that evolutionarily conserved AS of troponin-t in flight muscle of adult moths re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 41 publications
7
54
1
Order By: Relevance
“…A clear peak and subsequent fatigue is routinely seen during measurements of butterfly flight metabolic rate, suggesting that a true metabolic maximum is reached. Also, adding lead weights to the thorax did not increase peak flight metabolic rate in a moth measured using the same technique as in our experiments (Marden et al, 2008). Because peak metabolic rate may be more directly linked with fitness than RMR, we hope to see more work focused on metabolic capacity and lifespan.…”
Section: Relationship Between Metabolic Rate and Lifespanmentioning
confidence: 59%
See 1 more Smart Citation
“…A clear peak and subsequent fatigue is routinely seen during measurements of butterfly flight metabolic rate, suggesting that a true metabolic maximum is reached. Also, adding lead weights to the thorax did not increase peak flight metabolic rate in a moth measured using the same technique as in our experiments (Marden et al, 2008). Because peak metabolic rate may be more directly linked with fitness than RMR, we hope to see more work focused on metabolic capacity and lifespan.…”
Section: Relationship Between Metabolic Rate and Lifespanmentioning
confidence: 59%
“…An initially high RMR in newly eclosed individuals may result from a number of processes that take place in a maturing individual, such as egg development in females (Clifford and Woodring, 1986) and preparation of spermatophore production in males. Similarly, the flight muscles of young insects undergo maturation as exemplified by changes in muscle troponin T composition (Marden et al, 2008;Schippers et al, 2010). As the individual grows older, investment in these energy-consuming processes decreases.…”
Section: Repeated Measurements Of Resting and Flight Metabolic Ratesmentioning
confidence: 99%
“…In this regard, Marden and others showed that evolutionarily conserved alternative splicing of troponin-t in flight muscle of adult moths responds in a quantitative fashion to experimental manipulation of larval nutrition and adult body weight. 31 Overall, these results showed that alternative splicing of a gene expressed in muscle responds in a quantitative fashion to whole-organism variables, which apparently serves to coordinate muscle strength and energy expenditure with body condition and life history. Consistent with these findings, our results support the hypothesis that isoform expression responds to organism conditions to produce different isoform profiles that are associated with energetic and life-history traits.…”
Section: Discussionmentioning
confidence: 77%
“…A recent study of insect flight muscles demonstrated that there is precise quantitative variation in the relative abundance of alternatively spliced troponin T mRNA transcripts and protein isoforms in response to experimental manipulation of body weight and nutritional state (Marden et al, 2008). Here, we used rats to test the hypothesis that in a mammalian load-bearing (gastrocnemius) muscle, quantitative alternative pre-mRNA splicing of Tnnt3 is similarly regulated in response to natural and experimentally imposed variation in body weight.…”
Section: Introductionmentioning
confidence: 99%